Human α-galactosidase A is stimulated by folic acid supplementation – possible implications in Fabry disease management - Sabiha Khatoon; Mohammed A. Junaid (PLoS ONE, 2026)
Fabry disease (FD) in an inherited lysosomal storage disorder with severe lifelong issues if not therapeutically managed. The disorder results from mutation in the gene GLA causing the deficiency of lysosomal enzyme α-galactosidase A (AGLA) leading to accumulation of specific glycosphingolipids in several organs. Individuals suffering from FD are treated with either an enzyme replacement therapy providing injected recombinant enzyme or small molecule chaperone therapy through a specific inhibitor, 1-deoxygalactonojiromycin (DGJ), which allows partial folding of functional enzyme that is retained as misfolded protein consequent to mutations. These therapies suggest that any incremental increase in AGLA activity will be of benefit to individuals with FD. This study is aimed at providing evidence that the synthetic B-complex vitamin, folic acid (FA) necessary in preventing neural tube defects in babies, can significantly stimulate the expression and enzyme activity in human lymphoblastoid cells as well as recombinant AGLA, in a concentration dependent manner. The extent of FA mediated AGLA stimulation was similar in cells from male or female subjects. In the recombinant enzyme, the stimulation follows mixed type with increase in Vmax but without any effect on Km. We did not find any evidence of cytosine methylation in one CpG island in the GLA gene. FA also stimulated and protected AGLA activity that was inhibited with specific inhibitor, DGJ. FA was able to further stimulate DGJ mediated restoration of AGLA activity in lymphoblastoid cells from individual with FD. Such FA mediated stimulation of AGLA activity may offer benefit to individuals with FD.